2022
DOI: 10.3389/fnbot.2022.880073
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time EMG-Based Fixed-Bandwidth Frequency-Domain Embedded System for Robotic Hand

Abstract: The signals from electromyography (EMG) have been used for volitional control of robotic assistive devices with the challenges of performance improvement. Currently, the most common method of EMG signal processing for robot control is RMS (root mean square)-based algorithm, but system performance accuracy can be affected by noise or artifacts. This study hypothesized that the frequency bandwidths of noise and artifacts are beyond the main EMG signal frequency bandwidth, hence the fixed-bandwidth frequency-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Firstly, we relied on pattern recognition architectures, i.e. multinomial logistic regression and support vector machine, that can be easily implemented in micro-controllers [32], without requiring the high computational burden typically needed in practical contexts [33], [34].…”
Section: Additional Points and Limitationsmentioning
confidence: 99%
“…Firstly, we relied on pattern recognition architectures, i.e. multinomial logistic regression and support vector machine, that can be easily implemented in micro-controllers [32], without requiring the high computational burden typically needed in practical contexts [33], [34].…”
Section: Additional Points and Limitationsmentioning
confidence: 99%
“…For all time-and feature-domain measures, the measurement cycle was 1 kHz, and all features were calculated in parallel. Related studies [22][23][24][34][35][36][37][38][39] focused on pattern recognition accuracy between movements and predictions. In contrast, we aimed to measure the difference between paralyzed and normal functions.…”
Section: Rt Processingmentioning
confidence: 99%
“…Unlike previous RT processing studies [34][35][36][37][38][39], we found optimal values by adjusting window and shift sizes and considered the computer system capabilities related to each. In Table 3, "F" means "fail," "P" means "pass," and the number represents the number of samples.…”
Section: Rt Processingmentioning
confidence: 99%
“…Karheily et al used the STFT, the continuous WT, and Stockwell time-frequency domain characterization to classify hand motion, and reported an accuracy of 90.05%, 89.92%, and 90.96%, respectively [24]. Chen et al employed the STFT method to establish a STFT embedded system that detects muscle contraction, and reported an accuracy of up to 91.55% [25].…”
Section: Time-frequency Domain Analysismentioning
confidence: 99%